Role of active and passive smoking on lung cancer etiology in Mexico City Papel del tabaquismo activo y pasivo en la etiología del cáncer en la Ciudad de México - Francisco Franco-Marina; Jaime Villalba Caloca; Alexander Corcho-Berdugo (Instituto Nacional de Salud Pública, 2006)
OBJETIVE: To estimate the association between passive and active smoking exposures and lung cancer in Mexico City and the corresponding attributable risks. MATERIAL AND METHODS: Data was analyzed from a multicenter population-based case-control study conducted in Mexico City. RESULTS: ORs for lung cancer in ever smokers were 6.2 (95% CI 3.9-10.2) for males and 2.8 (95% CI 1.7-4.4) for females. Passive smoking at home showed an overall OR of 1.8 (95% CI 1.3-2.6), similar in both genders. Attributable risk for active smoking for both genders combined, and for males and females separately, was estimated at 55, 76 and 27%, respectively. Attributable risk for passive smoking at home was 17% for females, 3.9% for males and 12% for the entire population. CONCLUSIONS: In Mexico City smoking is attributable to a smaller proportion of lung cancer cases than in developed countries. This is explained by a lower intensity of smoking in the Mexican population. OBJETIVO: Estimar la asociación entre tabaquismo pasivo y activo y cáncer pulmonar (CP) en la Ciudad de México (CM), así como los riesgos atribuibles asociados. MATERIAL Y MÉTODOS: Se analiza un estudio multicéntrico de casos-controles con base poblacional, realizado en la CM. RESULTADOS: Las RM para CP en alguna vez fumadores fueron de 6.2 (IC 95% 3.9, 10.2) en hombres y 2.8 (IC 95% 1.7, 4.4) en mujeres. La exposición pasiva al tabaco mostró una RM en ambos sexos de 1.8 (IC 95% 1.3, 2.6), similar en ambos sexos. Los riesgos atribuibles asociados al tabaquismo activo para ambos sexos, hombres y mujeres fueron de 55, 76 y 27%, respectivamente. El riesgo atribuible para tabaquismo fue de 17% en mujeres, 3.9% en hombres y 12% en ambos sexos. CONCLUSIONES: En la CM el tabaquismo explica una fracción menor de casos de CP que el estimado en países desarrollados. Esto se debe a que en México la intensidad del tabaquismo es menor.